Epigenetic Enhancer Marks and Transcription Factor Binding Influence Vκ Gene Rearrangement in Pre-B Cells and Pro-B Cells - Kleiman, Eden; Loguercio, Salvatore; Feeney, Ann J. (Frontiers in Immunology, 2018)
To date there has not been a study directly comparing relative Igk rearrangement frequencies obtained from genomic DNA (gDNA) and cDNA and since each approach has potential biases, this is an important issue to clarify. Here we used deep sequencing to compare the unbiased gDNA and RNA Igk repertoire from the same pre-B cell pool. We find that ~20% of Vk genes have rearrangement frequencies ³2-fold up or down in RNA vs DNA libraries, including many members of the Vk3, Vk4, and Vk6 families. Regression analysis indicates Ikaros and E2A binding are associated with strong promoters. Within the pre-B cell repertoire, we observed that individual Vk genes rearranged at very different frequencies, and also displayed very different Jk usage. Regression analysis revealed that the greatly unequal Vk gene rearrangement frequencies are best predicted by epigenetic marks of enhancers. In particular, the levels of newly arising H3K4me1 peaks associated with many Vk genes in pre-B cells are most predictive of rearrangement levels. Since H3K4me1 is associated with long range chromatin interactions which are created during locus contraction, our data provides mechanistic insight into unequal rearrangement levels. Comparison of Igk rearrangements occurring in pro-B cells and pre-B cells from the same mice reveal a pro-B cell bias towards usage of Jk-distal Vk genes, particularly Vk10-96 and Vk1-135. Regression analysis indicates that PU.1 binding is the highest predictor of Vk gene rearrangement frequency in pro-B cells. Lastly, the repertoires of iEk-/- pre-B cells reveal that iEk actively influences Vk gene usage, particularly Vk3 family genes, overlapping with a zone of iEk regulated germline transcription. These represent new roles for iEk in addition to its critical function in promoting overall Igk rearrangement. Together, this study provides insight into many aspects of Igk repertoire formation.